Etnografi Ruang Instalasi Gawat Darurat (IGD): Relasi Dokter dan Pasien di Rumah Sakit Umum Kota Makassar - Muhammad Zainuddin Badollahi; Andi Hasbi (Department Anthropology, Faculty of Social and Political Sciences Hasanuddin University., 2018)
This study aims to, (1) determine the ethics of physician professionalism in relation to the relationships established between doctors-patients and established medical communication, (2) analyze differences in physician-patient relations using health insurance and general patients, (3) find out the kinship network patients who are instructed on medical treatment obtained. This research was conducted at the Emergency Room at RSUP X Makassar using a qualitative descriptive study. The methods used are observation and interviews with doctors and patients. This study shows that (1) the doctors did not pay attention to and run the SOP IGD so that there was miscommunication, (2) health insurance patients and the general got different treatment in medical treatment, (3) kinship network was very influential in the medical action given by the doctor to his patient